A dual‐tuned 13C/1H head coil for PET/MR hybrid neuroimaging: Development, attenuation correction, and first evaluation. Issue 11 (24th September 2018) - Oehmigen, Mark; Lindemann, Maike E.; Gratz, Marcel; Neji, Radhouene; Hammers, Alexander; Sauer, Michael; Lanz, Titus; Quick, Harald H.
Abstract : Purpose: This study aims to develop, implement, and evaluate a dual‐tuned 13 C/ 1 H head coil for integrated positron emission tomography/magnetic resonance (PET/MR) neuroimaging. The radiofrequency (RF) head coil is designed for optimized MR imaging performance and PET transparency and attenuation correction (AC) is applied for accurate PET quantification. Material and Methods: A dual‐tuned 13 C/ 1 H RF head coil featuring a 16‐rung birdcage was designed to be used for integrated PET/MR hybrid imaging. While the open birdcage design can be considered inherently PET transparent, all further electronic RF components were placed as far as possible outside of the field‐of‐view (FOV) of the PET detectors. The RF coil features a rigid geometry and thin‐walled casing. Attenuation correction of the RF head coil is performed by generating and applying a dedicated 3D CT‐based template attenuation map (μmap). Attenuation correction was systematically evaluated in phantom experiments using a large‐volume cylindrical emission phantom filled with 18‐F‐Fluordesoxyglucose (FDG) radiotracer. The PET/MR imaging performance and PET attenuation correction were then evaluated in a patient study including six patients. Results: The dual‐tuned RF head coil causes a mean relative attenuation difference of 8.8% across the volume of the cylindrical phantom, while the local relative differences range between 1% and 25%. Applying attenuation correction, the relative difference between the two measurements with and without RF coil is reduced to mean value of 0.5%, with local differences of ±3.6%. The quantitative results of the phantom measurements were corroborated by patient PET/MR measurements. Patient scans using the RF head coil show a decrease of PET signal of 5.17% ± 0.81% when compared to the setup without RF head coil in place, which served as a reference scan. When applying attenuation correction of the RF coil in the patient measurements, the mean difference to a measurement without RF coil was reduced to −0.87% ± 0.65%. Conclusion: A dual‐tuned 13 C/ 1 H RF head coil was designed and evaluated regarding its potential use in integrated PET/MR hybrid imaging. Attenuation correction was successfully applied. In conclusion, the RF head coil was successfully integrated into PET/MR hybrid imaging and can now be used for 13 C/ 1 H multinuclear hybrid neuroimaging in future studies.